2021
DOI: 10.3390/children8100922
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Traits of Impulse Control Behavior in School Children under Controlled Attention, Motor Function, and Perception

Abstract: This research surveyed the characteristics of the developmental traits of impulse control behavior in children through parent-report questionnaires. After matching for gender and attention behavior, as well as controlling for variables (motor and perception) which might confound impulse control, 710 participants (355 girls and 355 boys; grade, 1–5; age, 7–12 years) were recruited from a database of 1763 children. Results demonstrated that there was a significant difference between grade 1 and grade 5 in impuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…A head injury before the age of 5 has previously been shown to attenuate developmental declines in impulsivity (Fullerton, Jackson, Tuvblad, Raine, & Baker, 2019). On the other hand, studies showed that the later elementary school years (i.e., 8-11 years) are a transitional period for the development of impulse control (Chen et al, 2021). A more complex explanation may be that the UPPS reflects general impulsivity, which starts to decline already in early childhood (Schwartz, Connolly, & Alsolami, 2022) and therefore was implicated by mTBI before 3 years.…”
Section: Effect Of Age-at-injurymentioning
confidence: 99%
“…A head injury before the age of 5 has previously been shown to attenuate developmental declines in impulsivity (Fullerton, Jackson, Tuvblad, Raine, & Baker, 2019). On the other hand, studies showed that the later elementary school years (i.e., 8-11 years) are a transitional period for the development of impulse control (Chen et al, 2021). A more complex explanation may be that the UPPS reflects general impulsivity, which starts to decline already in early childhood (Schwartz, Connolly, & Alsolami, 2022) and therefore was implicated by mTBI before 3 years.…”
Section: Effect Of Age-at-injurymentioning
confidence: 99%
“…Semoglou, Alevriadou, and Tsapakidou [23] stated that early childhood education emphasizes the significance of fine motor tasks and the use of learning aids, and Spanaki et al [24] claimed that the fine motor training program had a positive effect upon the graph motor skills of kindergarten and early elementary school children. Chen et al [25] explained that motor exercises and activities will benefit all students with delays, but the larger the delay, the more important the training and the bigger its impact on academics. Robinson et al [26] explained that a mastery climate is an innovative and exceptional pedagogy for teaching children motor skills and encouraging physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Tingkah laku yang menantang seringkali muncul pada anak-anak prasekolah, yang dapat menjadi tantangan bagi orang tua untuk mengelolanya (Dworkin, 1988;Misirliyan et al, 2023). Anak prasekolah cenderung melakukan tindakan impulsif dan mengalami kesulitan dalam mengendalikan emosi (Chen et al, 2021;Tao et al, 2014), yang dapat muncul dalam bentuk tantrum, kemarahan, penolakan untuk mengikuti instruksi, dan perilaku tak terduga dalam situasi tertentu. Para ibu yang merawat anak-anak prasekolah seringkali merasa frustrasi dan cemas mengenai cara mengatasi dan merespons perilaku-perilaku tersebut (Hails et al, 2018).…”
unclassified